Mitochondrial abnormalities in neurodegenerative models and possible interventions: Focus on Alzheimer's disease, Parkinson's disease, Huntington's disease - Patcharapong Pantiya (2020)
© 2020 Elsevier B.V. and Mitochondria Research Society Mitochondrial abnormalities in the brain are considered early pathological changes in neurogenerative diseases, such as Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease (HD). The mitochondrial dysfunction in the brain can be induced by toxic proteins, including amyloid-beta (Aβ), phosphorylated tau, alpha-synuclein (α-syn) and mutant huntingtin (mtHTT). These proteins cause mitochondrial genome damage, increased oxidative stress, decreased mitochondrial membrane permeability, and diminished ATP production. Consequently, synaptic dysfunction, synaptic loss, neuronal apoptosis, and ultimately cognitive impairment are exhibited. Therefore, the restoration of mitochondrial abnormalities in the brain is an alternative intervention to delay the progression of neurodegenerative diseases in addition to reducing the level of toxic proteins, especially Aβ, and restored synaptic dysfunction by interventions. Here we comprehensively review mitochondrial alterations in the brain of neurodegenerative models, specifically AD, PD and HD, from both in vitro and in vivo studies. Additionally, the correlation between mitochondrial changes, cognitive function, and disease progression from in vivo studies is described. This review also summarizes interventions that possibly attenuate mitochondrial abnormalities in AD, PD and HD models from both in vitro and in vivo studies. This may lead to the introduction of novel therapies that target on brain mitochondria to delay the progression of AD, PD and HD.